Under Mounting Pressure: A History of Media Influence on Major League Baseball Steroid Policies - Dan DeIuliis; David DeIuliis (Journal of Applied Sports Management, 2013)
This research is interested in the relationships among media coverage, governmental legislation and Major League Baseball’s anabolic steroids testing policies. An analysis of patterns of media coverage, legislation, and adoption of tougher penalties are explored, followed by an analysis of specific legislation in an attempt to identify its specific goals and target populations. The paper first analyzes recent Supreme Court cases and current federal legislation to determine if Congress acted legally in investigating Major League Baseball. Beginning in the mid-1980s with the surfacing of these media reports and ending with baseball’s toughest policy implementation in 2005, it then tracks the pattern of media coverage influencing the enactment of tougher penalties in baseball. Finally, it will examine the goals and justifications of a specific piece of legislation, the Clean Sports Act of 2005. Because anabolic steroids remain a problem among teenage and amateur athletes, this revisitation of the issue from a communications perspective will allow administrators to more efficiently combat the problem and media professionals to more effectively cover it.
Keywords: Major League Baseball; anabolic steroids; Congress; Clean Sports Act